Sonographic Changes in Structure and Volume of Thyroid Gland after Local Intrasurgical Cryoexposure in Patients with Nodular Euthyroid Goiter - Khaziyev, Vadim V.; Tjazhelova, Olga V.; Makedonskaya, Valentina A. (Problems of Cryobiology and Cryomedicine, 2013)
Comparative ultrasonic assessment of the outcomes of standard (subtotal resection of thyroid gland (TG) lobe) and combined (involving local cryoexposure) surgical treatment on TG structure and volume in the patients with uninodular non-toxic goiter was performed. Intraoperative controlled cryoexposure was carried-out using autonomous cryosurgical instrument with applicator diameter of0.2 cmand temperature of tip contact area of –140 ...–180°C. Cryoexposure was performed in the tissue of TG lobe subjected to surgery; volume of the tissue was at least 1 cm3, the exposure was single, and lasted 1 minute, which provided a sufficient amount of intact residual thyroid parenchyma not exposed to cryonecrosis. It was revealed that the standard surgical intervention led to a long-lasting reactive inflammation in the residual thyroid tissue. Sonographic observation during 12 months revealed the signs of autoimmune thyroiditis appearance and progression in 70% of patients after standard surgery and in 30% of patients after administration of application of intrasurgial cryoexposure. The findings suggested that local cryoablation exhibited immunocorrecting and preventive influence on the development of autoimmune aggression against thyroid gland in the post-surgical period. Probl Cryobiol Cryomed 2013; 23(3):240–246.